Leaf trait network architecture shifts with species‐richness and climate across forests at continental scale - Ying Li; Congcong Liu; Lawren Sack; Li Xu; Mingxu Li; Jiahui Zhang; Nianpeng He (Ecology Letters, 2022)
Variation in the architecture of trait networks among ecosystems has been rarely quantified, but can provide high resolution of the contrasting adaptation of the whole phenotype. We constructed leaf trait networks (LTNs) from 35 structural, anatomical and compositional leaf traits for 394 tree species in nine forests from tropical to cold‐temperate zones in China. Our analyses supported the hypothesis that LTNs would increase in modular complexity across forests in parallel with species‐richness and climatic warmth and moisture, due to reduced phenotypic constraints and greater opportunities for niche differentiation. Additionally, we found that within LTNs, leaf economics traits including leaf thickness would have central importance, acting as hub traits with high connectivity due to their contributions to multiple functions. Across the continent, the greater species richness and trait diversity observed in forests under resource‐rich climates enable greater complexity in whole phenotype structure and function as indicated by the trait network architecture.